Internal standardization combined with dilute-and-shoot preparation of distilled alcoholic beverages for Cu determination by high-resolution continuum source flame atomic absorption spectrometry - Raposo, Jorge Luiz; de Oliveira, Adriana Paiva; Jones, Bradley Todd; Gomes Neto, José Anchieta [UNESP] (Elsevier B.V., 2012)
Internal standardization (IS) and dilute-and-shoot preparation of distilled alcoholic beverages were evaluated for the direct determination of Cu by high-resolution continuum source flame atomic absorption spectrometry. Among Bi, In, Sn and Te evaluated as internal standards, Bi and Te furnished best results. Calibration curves were built up by plotting A(cu)/A(Bi) and A(cu)/A(Te) versus Cu concentration (0.05-4.0 mg L-1) and linear correlation coefficients were 0.9994 and 0.9990, respectively. Contents of Cu in 22 commercial distilled beverages analyzed by the proposed method varied in the 0.029-3.608 mg L-1 interval. These results were in agreement (paired t-test) at 95% confidence level with those obtained by line source FAAS using standard addition calibration. Recoveries improved from 77-83% (without IS) to 99-101% (with IS) intervals. The relative standard deviation (n = 12) was 0.8-3.7% (IS-Bi), 0.4-4.4% (IS-Te), and 0.5-9.1% (without IS) and the limit of detection was ca. 5 mu\g L-1 using Bi or Te. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Copper; Distilled alcoholic beverages; Internal standardization; HR-CS FAAS